KONSERVASI TRADISIONAL TERHADAP SUMBERDAYA ALAM DI PULAU NUSA MANU DAN NUSA LEUN NEGERI SAWAI KECAMATAN SERAM UTARA, MALUKU TENGAH - Supardi, Ilham Saktiawan; Badaruddin, Ernywati; Kaya, Manuel (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The aim of this research is to determine traditional forms of conservation and the process of implementing traditional conservation on natural resources on the islands of Nusa Manu and Nusa Leun. The method used is the descriptive method, namely making systematic and accurate descriptions according to facts found in the field and examining in depth the norms applied in the implementation of traditional conservation of natural resources. Data obtained from interviews are in the form of traditional conservation on the islands of Nusa Manu and Nusa Leun. The results of data analysis show that there are Matakau, Mangroves on Nusa Manu Island, Marsegu big bats. Matakau was installed on Nusa Leun Island. There are 3 types of matakau owned by certain clans, namely, matakau liwa-liwa, matakau porobangka and matakau ilang jalang, the Sawai people make Nusa Leun island a place to cut down mangroves but not Nusa Manu island . People do not cut down mangroves on Nusa Manu Island because this island is used as a habitat by the people of Sawai Village. Nusa Manu Island has another name, namely Marsegu (bat) island, because this island is used as a habitat for approximately 10,000 Marsegu so that the people of Sawai Village and people who visit The island of Nusa Manu calls this island Marsegu Island and the meaning of Nusa Manu Island is Bird Island.